(untitled) (Research, Society and Development, 2024)
Autism Spectrum Disorder (ASD) affects neurological development, being characterized by difficulties in communication, social interaction and repetitive behaviors. Food selectivity is a common challenge in children with ASD, often associated with problems in sensory processing, impacting health and family dynamics as considered by the authors: Oliveira, Souza, Ferraz de Oliveira and Petroli Frutuoso. of more effective and inclusive strategies to promote the well-being of children on the autistic spectrum and their families. The research analyzed 20 autistic children, aged 3 to 17, treated at a specialized clinic, using anamnesis data and nutritional reassessment after one year of intervention. The introduction of new foods, acceptance of textures and eating autonomy were evaluated. Results showed that 95% of children expanded their food repertoire and 75% accepted new textures. Behavioral therapy, based on positive reinforcement and sensory integration, reduced food selectivity, promoting greater autonomy in meals and improving the quality of family life.